2015
DOI: 10.3389/fpls.2015.00462
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-induced abiotic stress tolerance and underlying mechanisms in plants

Abstract: Abiotic stresses (such as metals/metalloids, salinity, ozone, UV-B radiation, extreme temperatures, and drought) are among the most challenging threats to agricultural system and economic yield of crop plants. These stresses (in isolation and/or combination) induce numerous adverse effects in plants, impair biochemical/physiological and molecular processes, and eventually cause severe reductions in plant growth, development and overall productivity. Phytohormones have been recognized as a strong tool for susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
560
4
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 922 publications
(665 citation statements)
references
References 173 publications
22
560
4
11
Order By: Relevance
“…The results indicate and reiterate the previous finding of involvement of Salicylic acid in modifying abiotic stress response [7][8][9][10] . Cultivar specific modification of salt stress response by salicylic acid is very starkly evident.…”
Section: Sml-668 On 3rd and 6th Day After Imbibition In Different Tresupporting
confidence: 72%
“…The results indicate and reiterate the previous finding of involvement of Salicylic acid in modifying abiotic stress response [7][8][9][10] . Cultivar specific modification of salt stress response by salicylic acid is very starkly evident.…”
Section: Sml-668 On 3rd and 6th Day After Imbibition In Different Tresupporting
confidence: 72%
“…SA is known to mediate plant local and systemic responses against plant microbial pathogens and abiotic stresses (Vlot et al 2009;Khan et al 2015). It has been shown that exogenous application of SA increased the levels of resveratrol accumulating in cell cultures of V. amurensis and V. vinifera and up-regulated expression of PAL and STS genes (Kiselev et al 2007(Kiselev et al , 2010Xu et al 2015).…”
Section: Hormonal Regulation Of Stilbene Biosynthesismentioning
confidence: 99%
“…Alternatively, the exogenous application of kaolin (KL) and salicylic acid (SA) can be adequate short-term solutions to attenuate the adverse effects of summer associated stresses. KL is a white mineral clay that avoid the accumulation of heat load through the reflection of sunlight, reducing the risk of leaf and fruit damage from high temperatures and solar injury (Glenn and Puterka, 2004) and SA is a signaling phytohormone with diverse regulatory roles in plant metabolism and abiotic stress tolerance (Khan et al, 2015). However, the influence of these substances on crop quality have received less attention than the influence on yield, possibly because they are more difficult to detect and sometimes are not consensual.…”
Section: Introductionmentioning
confidence: 99%